Zasady metody etnogeograficznej w polskiej etnologii i jej perspektywy - Miśta, Rafał (Studia Etnologiczne i Antropologiczne, 2022)
The article is an attempt at collecting and discussing the procedures of the ethnogeographical method which have been used in Polish ethnology from the beginning of the twentieth century until today. The most important discussions of this method in the Polish scientific literature have been compiled, and on their basis a list synthesising its principles and heuristics has been created. The subsequent part of the article discusses how the ethnogeographic method as practised in Poland so far presents itself from the perspective of contemporary cartographic and statistical methods, especially from the viewpoint of research within the framework of cultural evolution and digital humanities.